Tegaserod maleate exerts anti-tumor effects on prostate cancer via repressing sonic hedgehog signaling pathway - Maoping Cai; Shengdong Ge; Yaying Hong; Yao Chen; Yang-Zi Ren; Dacai Zhong; Mingkun Chen; Yuan Liu; Zhe-Sheng Chen; Ninghan Feng; Zhanghui Chen; Shan-Chao Zhao (Molecular Medicine)
Abstract Prostate cancer (PCa) is a highly common type of malignancy and affects millions of men in the world since it is easy to recur or emerge therapy resistance. Therefore, it is urgent to find novel treatments for PCa patients. In the current study, we found that tegaserod maleate (TM), an FDA-approved agent, inhibited proliferation, colony formation, migration as well as invasion, caused the arrest of the cell cycle, and promoted apoptosis of PCa cells in vitro. In addition, TM suppressed the tumor growth in the cell-derived xenograft (CDX) mouse model in vivo. Mechanistically, TM exerted anti-tumor effects via downregulating GLI2, and its downtream targets, thus inhibiting the sonic hedgehog (SHH) signaling pathway. In brief, our findings demonstrated that TM effectively inhibited the activities of PCa cells by suppressing the SHH signaling pathway and provided a potential new agent for the treatment of PCa.